MO810INTERLEUKIN-6 (-174G/C) POLYMORPHISM, RS1800795, IN ESRD PATIENTS' OUTCOME*. (29th May 2021) - Rocha, Susana; Valente, Maria João; Coimbra, Susana; Catarino, Cristina; Rocha-Pereira, Petronila; Oliveira, José Gerardo; Madureira, José; Fernandes, João Carlos; Faria, Maria do Sameiro; Miranda, Vasco M P; Belo, Luís; Santos-Silva, Alice; et al.
Abstract: Background and Aims: Chronic inflammation plays an important role in the progression of chronic kidney disease (CKD) to end-stage renal disease (ESRD). The single nucleotide polymorphism (SNP) in the promoter region (-174G/C) of interleukin-6 (IL6) gene regulates the levels of this cytokine, which have been associated with a poor outcome in several pathologies. Our aims were to determine, according to the genotype distribution of this polymorphism, the association between the inflammatory mediators, high sensitivity C-reactive protein (hsCRP), IL6, and pentraxin 3 (PTX3), shown to be increased in ESRD, and to estimate the risk for all-cause mortality over a period of one year. Method: 289 ESRD patients on hemodialysis (high-flux hemodialysis and hemodiafiltration) were included in this study. Real-Time PCR TaqMan SNP genotyping assays were used to assess allelic frequencies of IL6 (rs1800795). We evaluated the circulating levels of PTX3, hsCRP and IL6 using commercially available kits. Deaths occurring along 1-year follow-up period were recorded, and the all-cause mortality hazard ratio (HR), according to IL6 polymorphisms in this patient cohort were determined by Cox regression analysis. A p < 0.05 value was considered statistically significant. Results: In all IL6 (-174G>C) genotypes, hsCRP was positively and significantly correlated with IL6. For hsCRP and PTX3, a positive correlation with significance was only found for the GG genotype. All genotypes showed positive correlations between IL6 and PTX3 circulating levels, although only the GG genotype achieved a significant value. The Cox regression survival analysis for all-cause mortality in ESRD patients, using as reference the heterozygous patients for IL6 polymorphism, showed that CC patients presented a significant higher mortality risk, with a HR of 3.275 [1.165 to 9.204]. Moreover, the median survival time of CC patients (100 [54 - 138] days) was lower than that presented by the GG genotype patients (211 [83 - 290] days, p < 0.05 vs. CC) and by the heterozygous patients (291 [72 - 332] days, p = 0.157 vs. CC). Conclusion: We observed different correlation profiles between inflammatory biomarkers within each IL6 (-174G>C) genotype. The association of the CC genotype of the IL6 polymorphism with a poorer outcome and shorter survival time for ESRD patients was also observed. However, further studies are required and must consider the underlying individual genetic background, since the inflammatory state appears to be influenced by IL6 polymorphisms, which, in turn, might be determinant for disease progression and outcome. Acknowledgments: This work was supported by Applied Molecular Biosciences Unit-UCIBIO, financed by national funds from FCT/MCTES (UIDB/04378/2020), by North Portugal Regional Coordination and Development Commission (CCDR-N)/NORTE2020/Portugal 2020 (Norte-01-0145-FEDER-000024) and by REQUIMTE-Rede de Química e Tecnologia-Associação in the form of a researcher (S. Rocha) – project Dial4Life co-financed by FCT/MCTES (PTDC/MEC-CAR/31322/2017) and FEDER/COMPETE 2020 (POCI-01-0145-FEDER-031322).